(untitled) (Research, Society and Development, 2021)
Aiming to characterize the floristic composition, diversity, horizontal structure, successional stage and the dynamics of land occupation of the forest fragment of a secondary forest area located in the periurban area of ​​the municipality of Belém, Pará. A Forest Census was carried out measuring all individuals with diameter greater than or equal to 15 cm and a sample inventory of eight permanent plots. The species were classified into ecological groups. As for composition and richness, a species listing was made and the sample representativeness was calculated among the different sample units. The dynamics of land occupation was performed using the Isodata method. In the Census, 2,163 individuals, 171 species and 51 botanical families were measured and in the sampling by plots, 2,309 individuals, 186 species and 52 families were found. Shannon’s diversity index was H ’= 4.35 nats.ind to an equability of J’ = 0.83, indicating a high floristic diversity in the area. The group of species with the most predominance was the late secondary species and in the multitemporal analysis of the soil cover it was possible to verify 95.8% is secondary forest in medium stage of regeneration. The dendrometric parameters of density and basal area had values close to those found in remnants of primary and secondary forests in the Amazon region; the edge environment presented floristic-structural parameters a little higher than the interior environment, with the exception of the basal area parameter which was greater inside the fragment and through the analysis of the successional and dynamic stage of the soil cover.